صيغة "فَعِيْل" ودلالاتها في سورتي هود ويوسف: دراسة صرفية تحليلية - Nur Sakinah binti Mohd Salleh (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
The title of this research is: Pattern “Fa'iil” And Its Connotations in Surah Hud and Surah Yusuf: Morphological and Analytical Study. This research contains the study of morphology, focusing on the pattern of “Fa'iil” and its connotation in Surah Hud and Surah Yusuf. The research employed morphological and analytical research method to discover the differences within the group of six patterns: hyperbolic participle, resembling participle, gerund, “Fa'iil” as active participle, or as passive participle, or as reactive participle. In order to complete the study, all of the “Fa'iil” patterns were collected from the two surah, and the connotation and meaning were analysed before determining the category of each word with this pattern in these two surah and the standard of differentiation between the six patterns mentioned above. This research also contains the theory of morphology and its relation with derived nouns, static nouns and derived nouns and their categories, Arabic nouns and verb patterns that resemble in meaning, and the connotation of “Fa'iil” in the group of six patterns. In the last part of the study, the research focuses on analysing this pattern in the two surah. As a result, the study reveals that the meaning determination of words depends on the root words, their transitive and intransitive verbs, the basic paradigms and the context of the sentence.